Distress tolerance in OCD and anxiety disorders, and its relationship with anxiety sensitivity and intolerance of uncertainty. (June 2015) - Laposa, Judith M.; Collimore, Kelsey C.; Hawley, Lance L.; Rector, Neil A.
Highlights: DT was negatively related to anxiety sensitivity and intolerance of uncertainty. DT scores predicted GAD, SAD and OCD symptoms, but not PD/A symptoms. DT lost significance when AS and IU were taken into account. There were no between group differences on DT. Abstract: There is a growing interest in the role of distress tolerance (i.e., the capacity to withstand negative emotions) in the onset and maintenance of anxiety. However, both empirical and theoretical knowledge regarding the role of distress tolerance in the anxiety disorders is relatively under examined. Accumulating evidence supports the relationship between difficulties tolerating distress and anxiety in nonclinical populations; however, very few studies have investigated distress tolerance in participants with diagnosed anxiety disorders. Individuals with social anxiety disorder (SAD), generalized anxiety disorder (GAD), panic disorder with and without agoraphobia (PD/A) and obsessive-compulsive disorder (OCD) completed measures of distress tolerance (DT), conceptually related measures (i.e., anxiety sensitivity (AS), intolerance of uncertainty (IU)), and anxiety symptom severity. Results showed that DT was negatively associated with AS and IU. DT was correlated with GAD, SAD and OCD symptoms, but not PD/A symptoms, in individuals with those respective anxiety disorders. DT was no longer a significant predictor of OCD or anxiety disorder symptom severity when AS and IU were also taken into account. There were no between group differences on DT across OCD and the anxiety disorder groups. Implications for the role of distress tolerance in anxiety pathology are discussed.